Kwashiorkor and intellectual development: a ten-year follow-up study - Evans, David E (Department of Psychology, 2016)
Forty Cape Coloured children who had been hospitalized for kwashiorkor in infancy were compared with their siblings on an intelligence test battery at the 10th year of follow-up. No significant differences in intelligence test performance were noted. A significant discrepancy between the intelligence test score and the drawing score on late onset cases may be due to affective factors. The groups were similar in terms of height, weight and head circumference. The differences between well-nourished and poorly nourished groups found by previous investigators may be accounted for by the independent operation of non-nutritive variables in the social and emotional environment. The use of intra-familial controls in the present study minimised these influences as well as possible genetic factors in intellectual development. Kwashiorkor is a protein calorie nutritional disease which occurs typically in children under the age of 2 years. The disease was recognised in the early 1930's, but only later was the nutritional aetiology realised. Today, kwashiorkor is regarded as a well-defined syndrome representing one pole of the broad clinical spectrum of nutritional disease referred to as protein-calorie malnutrition (PCM). In contrast to marasmus which represents the opposite end of the continuum, the caloric deficiency in kwashiorkor is not as severe as is the protein deficiency. The idea that kwashiorkor may affect the intellectual development of the child is suggested by the marked apathy during the acute stage of the disease.